Educational Service Quality in Vocational High Schools: The Role of Visionary Leadership, Teacher Competence, and Organizational Culture - Alamsyah Riky Wardana; Saiful Anwar; Siti Zubaidah (Mindset : Jurnal Pemikiran Pendidikan dan Pembelajaran, 2025)
This study examines the factors influencing educational service quality in vocational high schools, focusing on visionary leadership, teacher competence, and organizational culture. A quantitative survey design was employed, involving 111 teachers (n = 111) selected using a purposive sampling technique from private vocational high schools in Parung Panjang District, Bogor Regency. Data were analyzed using multiple linear regression with SPSS. The results reveal that visionary leadership, teacher competence, and organizational culture each have a positive and significant effect on educational service quality, both individually and simultaneously. Among these variables, teacher competence demonstrates the strongest influence, as indicated by the highest standardized coefficient (β = [insert value]), highlighting its dominant role in improving educational service quality. This study contributes to the literature by providing empirical evidence on the relative influence of leadership, competence, and organizational culture in shaping educational service quality within the context of Indonesian vocational education. The findings emphasize the importance of strengthening teacher competence, supported by effective leadership and a conducive organizational culture, to enhance the quality of educational services.